Impact of Post-Operative Complications on Quality of Life After Pancreatectomy - Mbah, Nsehniitooh; Brown, Russel E; St. Hill, Charles R; Bower, Matthew R; Ellis, Susan F; Scoggins, Charles R; McMasters, Kelly M; Martin, Robert CG (JOP. Journal of the Pancreas, 2012)
Purpose This study was undertaken to analyze the quality of life changes reported by patients with pancreatic cancer undergoing pancreatectomy. Design Post-hoc analysis was performed of a clinical trial examining the safety of intraoperative autotransfusion during oncologic resections. Main outcome measures Perioperative (90-day) complications were graded prospectively using a validated 5-point scale. Quality of life parameters were recorded prospectively by a single trained interviewer preoperatively, at the first post-operative outpatient visit, and at 6 weeks, 3 months, and 6 months follow-up using the EORTC QLQ-C30 and FACT-An instruments. Results Pancreatectomy for adenocarcinoma was performed in 34 patients with a median follow-up of 2 years (range: 1-1.5 years). Major (grade ≥ 3) complications occurred in 12 (35.3%) of patients. Early (<6 month) recurrence was noted in 2 patients (5.9%). Increased severity of fatigue, pain, dyspnea, and loss of appetite over baseline were noted at initial follow-up (P<0.05); however, symptom scores normalized at 6-week follow-up, and remained stable at 6 months. No significant difference was noted in quality of life metrics between patients with or without major complications (P>0.11). A significant (P=0.023) decline in cognitive function vs. baseline was noted at 6-month follow-up after pancreatectomy. Using a repeated-measures generalized linear model, neither age, nor complication occurrence, nor adjuvant therapy, nor early recurrence accounted for this cognitive decline (P>0.10). Conclusion Quality of life metrics tend to normalize to preoperative levels after pancreatectomy at 6 weeks post-operatively. The occurrence of major complications does not predict a decreased quality of life. The decrease in self-reported cognitive function at six months in this cohort merits further study. Image: FACT physical well-being.